A Method for Flexible Heat Exchanger Network Design under Severe Operation Uncertainty. Issue 5 (4th April 2013) - Zheng, K.; Lou, H. H.; Wang, J.; Cheng, F.
Abstract Most investigations on heat exchanger network (HEN) synthesis which plays an important role in improving the efficiency of industrial plants, focus on deterministic conditions whereas operational flexibility and feasibility are less concerned. In the real industrial world, each system experiences various disturbances due to changes in stream temperature, flow rate, and other uncertain factors. An approach for flexible HEN synthesis under severe operation uncertainty is proposed, which is represented by the Probability bounds analysis (PBA) theory and is sampled by a double‐loop sampling method. A case study, which generates a better solution with less total annual cost and good flexibility under severe uncertainty, demonstrates the capability of this simplified approach.